1994
DOI: 10.1210/jcem.78.6.8200950
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on type I collagen synthesis and degradation: further evidence for genetic regulation of bone turnover.

Abstract: Circulating osteocalcin, a marker of bone formation, is under strong genetic influence, and this effect is related to the genetic influence on bone density. To examine genetic influences on bone turnover further, other markers of bone formation (serum carboxyterminal propeptide of type I procollagen, PICP), bone resorption (serum pyridinoline cross-linked carboxyterminal telopeptide of type I collagen, ICTP), and nonosseous connective tissue synthesis (serum aminoterminal propeptide of type III procollagen, PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 35 publications
1
26
0
1
Order By: Relevance
“…Thus, the changes observed in these markers during bed rest are more clearly related to bed rest itself and/or the LBNP exercise. The heritability of these markers of bone resorption also provides a biochemical explanation for previously documented heritability of bone health [1,7,16,24,40]. The relatively high between-subject variability in bone markers is frequently criticized as limiting their utility, but our data suggest that the variability is likely related to genetics, and that studies to determine the causes of variability may reveal more about bone metabolism than expected.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the changes observed in these markers during bed rest are more clearly related to bed rest itself and/or the LBNP exercise. The heritability of these markers of bone resorption also provides a biochemical explanation for previously documented heritability of bone health [1,7,16,24,40]. The relatively high between-subject variability in bone markers is frequently criticized as limiting their utility, but our data suggest that the variability is likely related to genetics, and that studies to determine the causes of variability may reveal more about bone metabolism than expected.…”
Section: Discussionsupporting
confidence: 57%
“…Family-based studies have also yielded strong heritability estimates for BMD (Gueguen et al 1995), with effects that are maximal in young adults and persist even after adjusting for lifestyle factors that are known to regulate BMD (Krall & Dawson-Hughes 1993). Other determinants of osteoporotic fracture risk also have a heritable component, including: femoral neck geometry and hip axis length (Arden et al 1996, Flicker et al 1996, Slemenda et al 1996, ultrasound properties of bone (Arden et al 1996), biochemical markers of bone turnover (Morrison et al 1992, Tokita et al 1994, Garnero et al 1996, Harris et al 1998, body mass index (Carmichael & McGue 1995, Kaprio et al 1995, Arden & Spector 1997, muscle strength (Arden & Spector 1997), age at menarche (Kaprio et al 1995) and age at menopause (Snieder et al 1998). The data are conflicting with regard to the influence of genetic factors on bone loss; Christian et al (1989) found no evidence for a genetic effect on bone loss at the wrist in ageing male twins, whereas Kelly et al (1993) concluded that there were strong genetic effects on axial bone loss in female twins.…”
Section: What Is the Evidence For A Genetic Contribution To Osteoporomentioning
confidence: 99%
“…(10,11) Moreover, genetic factors also account for a large proportion of variance in risk factors for fracture, such as bone mineral density (BMD), (12) bone loss, (13) quantitative ultrasound, (14) and bone turnover markers. (15) Thus genetic factors may be useful in the prognosis of fracture. However, studies in the fields of diabetes (16) and cancer (17) suggested that genetic profiling contributed minimally to the prognosis of these diseases.…”
Section: Introductionmentioning
confidence: 99%